CGIAR Evaluation Policy - CGIAR Advisory Services Shared Secretariat (CGIAR Advisory Services, 2022)
The new CGIAR Evaluation Framework and revised CGIAR Evaluation Policy were approved by the CGIAR System Board in February 2022 and endorsed by the System Council, the CGIAR strategic decision-making body, that took place on 8-9 March 2022. The new Evaluation Framework sets the overall approach to process and performance evaluations in CGIAR with mandatory overarching principles and standards, whereas the Evaluation Policy details the evaluation criteria, complementarities, roles and responsibilities.